Development of a provisional core set of response measures for clinical trials of systemic sclerosis. Issue 5 (24th September 2007) - Khanna, D; Lovell, D J; Giannini, E; Clements, P J; Merkel, P A; Seibold, J R; Matucci-Cerinic, M; Denton, C P; Mayes, M D; Steen, V D; Varga, J; Furst, D E; et al.
Abstract : Objective: To develop a provisional core set of response measures for clinical trials of systemic sclerosis (SSc). Methods: The Scleroderma Clinical Trials Consortium (SCTC) conducted a structured, 3-round Delphi exercise to reach consensus on a core set of measures for clinical trials of SSc. Round 1 asked the SCTC investigators to list items in 11 pre-defined domains (skin, musculoskeletal, cardiac, pulmonary, cardio-pulmonary, gastrointestinal, renal, Raynaud phenomenon and digital ulcers, health-related quality of life and function, global health, and biomarkers) for SSc clinical trials. Round 2 asked respondents to rate the importance of the chosen items and was followed by a meeting, during which the Steering Committee discussed the feasibility, reliability, redundancy and validity of the items. Round 3 sought to obtain broader consensus on the core set measures. Members also voted on items that had data on feasibility but lacked data on reliability and validity, but may still be useful research outcome measures for future trials. Results: A total of 50 SCTC investigators participated in round 1, providing 212 unique items for the 11 domains. In all, 46 (92%) participants responded in round 2 and rated 177 items. The ratings of 177 items were reviewed by the Steering Committee and 31 items from the 11 domains were judged to be appropriate for inclusion in a 1-year multi-centre clinical trial. In total, 40 SCTC investigators completed round 3 and ranked 30 of 31 items as acceptable for inclusion in the core set. The Steering Committee also proposed 14 items for a research agenda. Conclusion: Using a Delphi exercise, we have developed a provisional core set of measures for assessment of disease activity and severity in clinical trials of SSc.